Endangered species of vascular plants of Kutno - Warcholińska, Urszula; Gmerek, Anna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
In this article a list and characterization of endangered species of vascular plants, found in the area of Kutno in 1992-1994, has been presented. The research was carried out using a cartogram method.